The study of soaking and germination times to improve the nutritional quality of white and black glutinous rice - Phan, Man V.; Tran, Hai C.; Pham, Hanh T.H.; Le, Thanh T. (Asia-Pacific Journal of Science and Technology, 2022)
This study examined the effect of soaking and sprouting times on germination rates, biochemical (protein, lipid, and carbohydrate), and phytochemical contents gamma-amino butyric acid (GABA), gamma-oryzanol, tocopherols, and B vitamins in dehulled white and black glutinous rice (N97 and DH6). The dehulled white and black glutinous rice (N97 and DH6) were soaked in distilled water for 2, 4, 6, and 8 h at 30 °C. Then, they were germinated for 12, 24, 36 h at room temperature under an aerobic condition (RH%=83-85%). The results showed that the germination rates were positively correlated to the soaking time and the germination time. Specifically, at the soaking time of 6 h and the germination time of 24 h, the germination rate of dehulled white and black glutinous rice cultivars (N97 and DH6) achieved maximum values (97.98% and 95.19%, respectively). The results also showed that the biochemical and phytochemical contents of the germinated rice were substantially improved at 6 h of soaking and 24 h of sprouting. The extended soaking (8 h) and germination periods (36 h) caused the degradation of the biochemical (i.e., protein, lipid, carbohydrate) and phytochemical contents (i.e., GABA, tocopherol, gamma- oryzanol, and vitamins), which resulted in the low nutritional values of the germinated rice. The results of this study are expected to offer a possible solution to the improvement of the germinated rice quality associated with the soaking and germination conditions.